2019
DOI: 10.1021/acs.iecr.9b04998
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Enhancement of the Extraction and Separation Efficiencies of Lanthanoid(III) Ions by the Formation of Charged Adducts in an Ionic Liquid

Abstract: The synergistic ionic-liquid extraction and extraction equilibrium of lanthanoid(III) (Ln(III)) ions have been investigated using 2-thenoyltrifluoroacetone (Htta) and trioctylphosphine oxide (TOPO) in the ionic liquid 1-butyl-3methylimidazolium bis(trifluoromethanesulfonyl)imide ([C 4 mim][Tf 2 N]). The selective synergistic effect for heavier Ln(III) ions was found using a combination of Htta and TOPO in [C 4 mim][Tf 2 N], leading to enhanced separability among Ln(III) ions. The extracted Ln(III) species and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 49 publications
1
12
0
1
Order By: Relevance
“…Figure 2(a), the %E of Ce complex was higher than La(III) complex. [9]. Additionally, it was found that the separation of Lns(III) varied with the acidity of the β-diketones, for example, the SF between Eu(III) and Lu(III) in the synergistic system using benzoylacetone (Hba) with a higher pKa is significantly larger than those with the other β-diketones [11].…”
Section: Solvent Extraction Of La(iii) and Ce(iii) Complexesmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 2(a), the %E of Ce complex was higher than La(III) complex. [9]. Additionally, it was found that the separation of Lns(III) varied with the acidity of the β-diketones, for example, the SF between Eu(III) and Lu(III) in the synergistic system using benzoylacetone (Hba) with a higher pKa is significantly larger than those with the other β-diketones [11].…”
Section: Solvent Extraction Of La(iii) and Ce(iii) Complexesmentioning
confidence: 99%
“…The synergistic extractability and the separation factor (SF) can be ascribed to the adduct formation of Ln(III)-β-diketones with neutral ligands in the organic phase and lowered with an increase in the atomic number of Ln(III) in the β-diketone-TOPO [9] [10]. Also, Okamura et al, found that the SF between La and Ce, Pr and Nd, Sm and Eu, and Eu and Gd with Htta and TOPO in [C 4 mim][Tf 2 N] is higher than that with D2EHPA or PC-88A in isooctane [9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations